Philosophical Practices in the Context of a University Master’s Degree Program - Cipolletta, Patrizia (B@belonline, 2022)
The text traces the preparatory interview for 16th International Conference on Philosophical Practice organized in 2020 in S. Petersburg and postponed due to Covid. The interview presents Master’s degree programme in Philosophical Counseling, established at the University of Roma Tre in 2006, and illustrates the activities of the association Agàpe School. Training in philosophical counseling and philosophical practices within the university Master. The Master programme focuses on the importance of the dialogue between the practitioners that daily deal with the classical and grounding texts of the philosophical tradition, moved by both historical and linguistic rigorous approaches, and the counselors, who listen, in their philosophical practices, to the urgent questions that arise from the everyday life of society. In such a mutual exchange, the practical approach to philosophy allow them, on the one hand, to constantly go back to the sources of the philosophical wisdom as well as to merge into the dialogue between philosophy and sciences, and, on the other, the philosophical research can hearken the problems of the plurality, which inhabits modern societies, reenacting the ancient philosophical practice that always strives for the good and the flourishing life.